Nieznany list Jana Kasprowicza - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article constitutes an edition of a previously-unpublished letter by Jan Kasprowicz. The epistolary testament offers some new knowledge about the poet’s life and work, especially in the area of translation.